2014
DOI: 10.1016/j.bjorl.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and placement of cartilage island graft in tympanoplasty

Abstract: If cartilage graft is properly prepared and placed, cartilage graft tympanoplasty appears to provide better success rates and hearing results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…Therefore, cartilage graft materials are preferred for large perforations. 13 Kazikdas et al found 95.7% graft success rate for palisade cartilage graft, compared with 75% for temporalis fascia grafts. 14 …”
Section: Discussionmentioning
confidence: 98%
“…Therefore, cartilage graft materials are preferred for large perforations. 13 Kazikdas et al found 95.7% graft success rate for palisade cartilage graft, compared with 75% for temporalis fascia grafts. 14 …”
Section: Discussionmentioning
confidence: 98%
“…It receives its nutrients by diffusion and perichondrial attachment on one side increases its 16 The main advantage of cartilage tympanoplasty is that epithelisation may continue over the cartilage surface even if the graft detaches anteriorly. 17 The other advantage is that cartilage tympanoplasty avoids synechia formation between the graft and promontory, because there is no need to use absorbable gelatin sponge in the middle ear to support the graft. 17 Therefore, cartilage has now become the preferred graft material over temporalis fascia in high risk perforations.…”
Section: Discussionmentioning
confidence: 99%
“…17 The other advantage is that cartilage tympanoplasty avoids synechia formation between the graft and promontory, because there is no need to use absorbable gelatin sponge in the middle ear to support the graft. 17 Therefore, cartilage has now become the preferred graft material over temporalis fascia in high risk perforations. Cartilage graft was first described Heerman in 1962.…”
Section: Discussionmentioning
confidence: 99%
“…Causes of tympanoplasty failure using a temporal muscle fascia graft included severe ear pathologies, pathology of the malleus handle and stapes arch revision surgery, atelectasis, cholesteatoma, tympanosclerosis, large (>50% of total tympanic membrane diameter) and anterior perforations, tobacco smoke exposure, perforation drainage during surgery, and bilateral disease. 12 All the patients underwent revision tympanoplasty with cartilage-perichondrium composite island graft, done using underlay technique after slicing the cartilage with help of cartilage slicer. Ossiculoplasty was performed as and when needed.…”
Section: Discussionmentioning
confidence: 99%